Adapting a measure of quality of life to children with Down Syndrome for the development of evidence-based interventions - Gómez Sánchez, Laura Elisabet ([Madrid] : Colegio Oficial de Psicólogos de Madrid, 2020)
Research has highlighted that no instrument with adequate evidence of validity and reliability currently exists to assess quality of life (QoL) in children with Down syndrome (DS). Important limitations have been pointed out when existing QoL instruments for children with intellectual disability are applied to this population. The main goal of this research is to adapt the KidsLife scale by selecting the most reliable and discriminant items for children and youth with DS. The sample was composed of 405 children with DS, aged between 4 and 21 years old, attending organizations that provide educational, social, and health services. The field-test version of the KidsLife scale was administered as an informant- report, completed by someone who knew the child well, and who had opportunities to observe him/her over long periods of time in different situations. Evidence of reliability and validity based on the internal structure of the scale is provided. According to the QoL model used to develop the scale, the solution showing the best fit to the data was the one with eight intercorrelated domains. Finally, the implications of the study, its limitations and suggestions for future research are discussed.
Descripción basada en Psychosocial Intervention, vol. 29, núm. 1 (january 2020), P. 39-48.
Descripción basada en metadatos suministrados por el editor y otras fuentes.
Recurso electrónico. Santa Fe, Arg.: elibro, 2023. Disponible vía World Wide Web. El acceso puede estar limitado para las bibliotecas afiliadas a elibro.
Keywords: Calidad de vida.Virus de inmunodeficiencia adquirida (VIH).Lipodistrofia.; Evaluación.; Jóvenes.; Síndrome de Down; Validez; Artículos.